Assessment of growth and mortality parameters and exploitation rate to monitor the population status of wild catfish, Pangasius nasutus (Bleeker, 1863) in Pahang River, Malaysia - Jaafar, Mohd Basid; Arshad, Aziz; Abd Ghaffar, Mazlan; Wong, Nur Leena Wai Sin; Mat Piah, Rumeaida (Iranian Society of Ichthyology, 2023)
Pangasius nasutus is one of the popular freshwater fish species in Pahang River, Malaysia because of its economic value, however, the high exploitation rate, occurrence of invasive alien species in the same ecosystem, and habitat modification threatened its population sustainability. This study aimed to enhance the existing information database of a species that has limited data availability and to monitor its population status. The monthly samplings were conducted from the upstream to the downstream of the Pahang River for 12 consecutive months from May 2021 to April 2022. The FiSAT II software was used to analyse population parameters from the length frequency data. The results revealed the asymptotic length (Lˆž) = 661.50 mm, growth coefficient (K) = 0.18 year-1 , growth performance index (˜) = 4.90, the maximum age (Tmax) = 16.67, total mortality (Z) = 0.61 year-1 , natural mortality (M) = 0.25 year-1 , fishing mortality (F) = 0.36 year-1 and exploitation rate (E) = 0.59 year-1 . The results also showed that P. nasutus exhibits a slow growth rate, rendering it more susceptible to overfishing. This study also indicated that the current level of exploitation of P. nasutus population in the Pahang River appears to be appropriate. However, it is recommended that a precautionary strategy be adopted to mitigate the risk of overexploitation.